Multiple ossified intracranial and spinal meningiomas: a rare case report and literature review - Wang, Jian; Zhang, Anbang; Wang, Boya; Yuan, Jingmeng; Zhu, Junchi; Li, Mengjiao; Liu, Henli; Cheng, Lijuan; Kong, Ping (Frontiers in Neurology, 2023)
Ossified intracranial meningiomas (OIM) and ossified spinal meningiomas (OSM) are rare neoplasms of mesenchymal origin that predominantly manifest in the spinal cord and infrequently in the cranial region, accounting for ~0. 7–5.5% of all meningiomas. It is extremely rare to have multiple intracranial and spinal lesions accompanied by ossification. Herein, we report this rare case for the first time. A 34-year-old woman presented with paresthesia and limb weakness in the right lower limb and gradually worsened. Approximately half a year later, she could only walk with crutches. Magnetic resonance imaging of the brain and spinal cord showed multiple meningiomas, and histopathological examination confirmed multiple OIM and OSM (WHO grade 1). Multiple OIM and OSM are extremely rare with diverse imaging features, and it is easily confused with other tumors. Histopathological examination is the final diagnostic method.